2023
DOI: 10.1002/idm2.12122
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional multicellular biomaterial platforms for biomedical application

Jianxin Hao,
Chen Qin,
Chengtie Wu

Abstract: The three‐dimensional (3D) multicellular platforms prepared by cells or biomaterials have been widely applied in biomedical fields for the regeneration of complex tissues, the exploration of cell crosstalk, and the establishment of tissue physiological and pathological models. Compared with the traditional 2D culture methods, the 3D multicellular platforms are easier to adjust the components and structures of extracellular matrix (ECM) because of the synthesis of ECM by cells and the use of biomaterials. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…As a bioadhesive, the biocompatibility of the TPFe bioadhesive is crucial. , The cytocompatibility of the TPFe bioadhesive was investigated by a leaching mode test. As can be seen from Figure a,b, the cell viability of the TPFe bioadhesive group was greater than 99%, indicating that the TPFe bioadhesive had good cytocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…As a bioadhesive, the biocompatibility of the TPFe bioadhesive is crucial. , The cytocompatibility of the TPFe bioadhesive was investigated by a leaching mode test. As can be seen from Figure a,b, the cell viability of the TPFe bioadhesive group was greater than 99%, indicating that the TPFe bioadhesive had good cytocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al strategically utilized encapsulation of cells in an oxygen-consuming shell comprised of polydopamine, laccase, and tannic acid to enhance their hydrogen production efficiency . Recent investigations of the function of extracellular electron transfer and reverse electron transfer chains between microorganisms and solid semiconductive materials have led to the development of advanced biotic–abiotic hybrid systems containing a combination of bacteria and inorganic materials. , These materials have great potential for use in chemical processes that are driven by a combination of photocatalysis, electrocatalysis, and biocatalysis. Importantly, biotic–abiotic hybrid systems have been developed in hydrogen production. For instance, Xiong et al constructed the S.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the factors that induce the mineralization of COL I involve a family of small integrin-binding ligands, n -linked glycoproteins (SIBLINGs) in the extracellular matrix (ECM) and artificial biomolecules. 3–6 Although the hierarchical nature of the COL I fibril mineralization mechanism has been demonstrated in several studies by introducing these macromolecules into the mineralization system, the reasons why the PDL space is maintained unmineralized are ambiguous.…”
Section: Introductionmentioning
confidence: 99%